1998
DOI: 10.1007/s100480050028
|View full text |Cite
|
Sign up to set email alerts
|

Genetic fine mapping of the Miyoshi myopathy locus and exclusion of eight candidate genes

Abstract: Miyoshi myopathy (MM) is an early adult-onset, autosomal recessive disorder characterized by weakness and muscular atrophy starting in the distal muscles. The disease locus has been previously mapped by linkage analysis to chromosome 2p using the microsatellite marker D2S291. Initial haplotype analysis of markers in families from three different origins (North American, Japanese, and Tunisian) suggested that the MM gene is located in a 4-cM region flanked by markers D2S292 on the telomeric side and D2S286 on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…This high-resolution PAC contig resolved the marker order discrepancies in previous studies 6,8,13 . The physical size of the PAC contig also indicated that the previous minimal size estimation based on YAC mapping data was underestimated.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…This high-resolution PAC contig resolved the marker order discrepancies in previous studies 6,8,13 . The physical size of the PAC contig also indicated that the previous minimal size estimation based on YAC mapping data was underestimated.…”
Section: Introductionsupporting
confidence: 59%
“…Subsequently, our genetic mapping in MM families placed the MM locus between markers GGAA-P7430 and D2S2109 (ref. 6). At approximately the same time, Bushby and colleagues localized limb-girdle muscular dystrophy (LGMD-2B) to the same genetic interval 7−9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the region on 2p13, the loci for at least three other neuromuscular disorders have been mapped (Table 2): LGMD2B, 26 -28 MM7, 29 and a recently described Spanish distal anterior compartment myopathy (DACM). 30 Furthermore, a distal myopathy of slow progression has been described in a Russian LGMD2B family, 31,32 in which both disorders share a common haplotype.…”
Section: Discussionmentioning
confidence: 99%
“…Without a clear functional or positional candidate, we have identified LGMD2B by positional cloning 22,23 . This novel gene on chromosome 2p13 is highly expressed in muscle.…”
Section: Introductionmentioning
confidence: 99%